Evaluation of Integrated Coastal Zone Management Plan Practices in the Turkish Case - Ozugul, M. Doruk; Yerliyurt, Bora; Secilmisler, Tore (IOP PUBLISHING LTD, 2017)
In terms of both international and national contexts, mostly coastal zones are the place of complexity, vulnerability and competition, so that they have to be well-planned and managed. Diversity in users, land uses, investments, sectoral plans and policies make coastal areas highly complex and problematic zones where competition also takes place. Unless these dimensions of pressure aren't balanced with precautionary actions, coastal zones transform into more vulnerable geographies. Within this context Integrated Coastal Zone Management (ICZM) Plan appears as a major tool where integration becomes a vital keyword for such diversifying environments. This integration challenge covers sectoral, administrative, spatial, interdisciplinary (in terms of scientific research fields) and internationality dimensions. A set of basic principles could also be obtained from the literature in order to reach a better ICZM Plan practice. These could be summarized as; a broader perspective, a long-term perspective, adaptive management and monitoring, local specificities, specific solutions and flexible measures, carrying capacity of ecosystems, a participatory process, well coordination of policies and partners and coherence between sectoral policy objectives, planning and management. A similar problematic conceptualization is also viable for Turkey, where approximately 76% of the total border length and 27 of 81 provinces are coastal. Naturally, both ICZM and coastal zone planning are within the emerging planning issues of national agenda. The purpose of this paper is to examine the Turkish practices depending on the above-mentioned principles by comparing various official ICZM plans of selected provinces. As a general conclusion it is seen that ICZM-to be an integrative and multi-dimensional tool-is contextually misunderstood. From this perspective the determination of the plan borders, unsuitability of the plan contents with the ideal ICZM plans and absence of legal basiscould be defined as the major discussion topics which reflect the dilemmas of ICZM practice in the Turkish case.
Keywords: Architecture; Engineering; Materials Science; Urban Studies